PROMOSI KESEHATAN DENGAN METODE BEHAVIORAL CHANGE PADA ANGKA TEMUAN PASIEN SKABIES DI SEMUA CABANG KLINIK DERMA JAWA TENGAH - Ernada, Nindya Widyani; Suwarni, Sri; Indrasari, Ferika; Leki, Karol Giovani Battista; Kusumaningtyas, Aprilia (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2022)
Clinics as health care facilities also play a role in promotive and preventive. Scabies is an infectious skin disease caused by Sarcoptes scabei variant hominis which can be transmitted through direct human contact. This study aims to determine the effect of knowledge level and public health status to change patient behavior to live clean and healthy with behavioral change analysis of scabies rates in all branches of Kinik Derma Central Java. This type of research is observational with cross sectional design, purposive sampling technique. The population is all patients who come to the Derma clinic with a diagnosis of scabies in the January-April 2021 period. This research instrument uses a questionnaire sheet with the application of behavioral change measurement indicators, while for the diagnosis of scabies using the results of medical examination records. Data presentation is presented in the form of Histograms and percentages. The average knowledge of people with scabies answering about scabies disease is 78.02% answering correctly and for the average healthy and clean behavior (personal hygine) is 70.20%. Providing health promotion for the application of behavioral change methods used health promotion by providing brochures and IEC (Information Communication and Education) at the time of drug collection. When waiting for the medicine, it is also expected to see video shows on the Derma Clinic television screen. After a period of 2 months from the initial findings, the number of patients with scabies in all branches of Derma Clinic Central Java decreased by 24 patients or 20% of the number of patients at the beginning of the study.